Effect of colostrum quantity and quality on neonatal calf diarrhoea due to Cryptosporidium spp. infection - Arsenopoulos, K. (Comp Immunol Microbiol Infect Dis, 2017)
This study was conducted to assess the effect of colostrum quality and quantity on Cryptosporidium spp. calf diarrhoea in an intensive dairy cattle farm in Greece. Faecal samples were collected from 100 dairy calves randomly selected and born during all 4 seasons (March 2015 to May 2016) of the year. In total, 71% of the selected calves were positive for Cryptosporidium spp. oocysts. The statistical analysis revealed influence of colostrum quality on faecal score. Linear regression showed that the colostrum quantity during the first day of life was negatively associated with the number of Cryptosporidium spp. oocysts in faeces. During multivariable analysis, the variables representing the quality of colostrum and the season of the calf’s birth were identified as confounders. Cryptosporidium spp. is a common pathogen participating in neonatal calf diarrhoea. Colostrum management and season influence the number of Cryprosporidium spp. oocysts and faecal consistency. The above findings demonstrate novel risk factors that should be included in the strategic approaches to control cryptosporidiosis in newborn calves.